Implementasi Program Kota Tanpa Kumuh (KOTAKU) Di Kelurahan Purbalingga Kidul Kecamatan Purbalingga Kabupaten Purbalingga - Laras Saketi; Ngalimun Ngalimun; Denok Kurniasih (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2020)
Policy implementation is the implementation of a policy so that the objectives of the policy can be achieved. Implementation in terms of reducing slum area is one of the problems in Indonesia. The problem in this study was motivated by the lack of fulfillment of clean water needs, the people who participated less in the implementation of the KOTAKU program, and the absence of policies that supported the KOTAKU Program in the Purbalingga Kidul Village. This study aims to determine how much influence the idealized policy, target group, implementing organization and environmental factors have on the successful implementation of the No Slum City Program (KOTAKU) in the Purbalingga Kidul Village. The research method used was quantitative associative with a sample of 116 respondents and the sampling technique used the census method or total sampling. The analytical method used is Kendall Tau-c Correlation, Kendall W Concordance Coefficient and Ordinal Regression Analysis. The results of the study show that: (1) There is a positive and significant influence between the idealized policy on the success of the implementation and the regression coefficient of 0.608. (2) There is a positive and significant influence between the target group on the success of the implementation with a regression coefficient of 0.413. (3) There is a positive and significant influence between implementing organization on the success of implementation with a regression coefficient of 0.645. (4) There is a positive and significant influence between the environmental factors on the success of the implementation with a regression coefficient of 0.706. (5) There is a positive and significant influence between idealized policy, target group, implementing organization and environmental factors on the success of implementation with a regression coefficient of 0.824.